Preparation and Characterization of Nano-Fe3O4 and Its Application for C18-Functionalized Magnetic Nanomaterials Used as Chromatographic Packing Materials - Wen-Xin Liu; Wei-Na Zhou; Shuang Song; Yong-Gang Zhao; Yin Lu (Nanomaterials, 2023)
A new type of magnetic nanomaterial with Fe3O4 as the core and organic polymer as the shell was synthesized by seed emulsion polymerization. This material not only overcomes the problem of insufficient mechanical strength of the organic polymer, it also solves the problem that Fe3O4 is prone to oxidation and agglomeration. In order to make the particle size of Fe3O4 meet the requirement of the seed, the solvothermal method was used to prepare Fe3O4. The effects of the reaction time, amount of solvent, pH value, and polyethylene glycol (PEG) on the particle size of Fe3O4 were investigated. In addition, in order to accelerate the reaction rate, the feasibility of preparing Fe3O4 by microwave was studied. The results showed that under the optimum conditions, the particle size of Fe3O4 could reach 400 nm and had good magnetic properties. After three stages of oleic acid coating, seed emulsion polymerization, and C18 modification, the obtained C18-functionalized magnetic nanomaterials were used for the preparation of the chromatographic column. Under optimal conditions, stepwise elution significantly shortened the elution time of sulfamethyldiazine, sulfamethazine, sulfamethoxypyridazine, and sulfamethoxazole while still achieving a baseline separation.